Learning Resilience in Adult Education - Bzymek, Agnieszka (Przegląd Badań Edukacyjnych (Educational Studies Review), 2024)
The following article presents a pedagogical conceptualisation of resilience. In reference to adult education, this category will be analysed as a reflection grounded in an empirical study. Using the autobiographical method, I presented narrative interviews conducted with individuals under the care of the Daily Support Centre in Poland. Narrative biography has not only become a tool for learning about the stories of senior citizens but, for them, it was also a way of learning resilience, fulfilling an autotherapeutic function. In the article, I present the theoretical framework of the phenomenon in question and collate it to the functioning of elderly persons, thus demonstrating that the socio-emotional development in late old age is not only possible, but particularly desirable in the face of uncertainty, loneliness and the mental requirements of the modern world (Dominice, 2007, pp. 28–29). The adopted autobiographical method is treated as one of the forms of support. Therefore, the Author does not refer in detail to the analyses of the conducted interviews, taking into account their extensiveness. I indicate only selected aspects without performing a complete research analysis of the presented narrations, referring mainly to the central analytical categories: risk factors and protective factors. The article also contains other suggestions for shaping resilience in adults. Finally, it was created based on research experience on humans; regenerative and learning abilities in late adulthood.